Myanmar : 2018 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Myanmar. - International Monetary Fund. Asia and Pacific Dept. (Washington, D.C. : International Monetary Fund, 2019)
This 2018 Article IV Consultation highlights that Myanmar's economy is expected to gain steam albeit at a somewhat slower pace than previously envisaged but faces greater downside risks including from the crisis in Rakhine state. The country's long-term prospects remain strong, supported by a growing demographic dividend, a competitive labor force and its strategic location. The discussions recommend that successful implementation of the second wave of reforms in the Myanmar Sustainable Development Plan with a focus on peace, stability and good governance will help sustain the growth take-off and achieve the Sustainable Development Goals (SDGs). Financial regulations and supervision should be strengthened with a view to ensuring financial stability and deepening, while forming contingency plans to address systemic banking risks, and strengthening the resolution framework. Fiscal policy should be directed towards SDG-related spending, while lowering Central Bank of Myanmar financing and ensuring debt sustainability. The business environment is expected to benefit from upgraded infrastructure, access to finance, and strengthening of the overall governance framework.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet